Assessing the food web impacts of an anadromous Arctic charr introduction to a sub‐Arctic watershed using stable isotopes. (13th February 2013) - Murdoch, A.; Klein, G.; Doidge, D. W.; Power, M.
Abstract: Anadromous Arctic charr, Salvelinus alpinus (L.), was introduced to a sub‐Arctic river–lake system near the village of Kujjuuaq, Nunavik, and the stable isotope values and diets of key resident fish species were used to assess changes in feeding patterns. Stable isotope values for most species did not differ significantly between the pre‐ and post‐introduction periods, with observed shifts being within the bounds of expected natural variation. Lake chub, Couesius plumbeus (Agassiz), were the single species to show a difference between study periods, with a small but significant increase in δ 15 N. No significant post‐introduction changes were seen in lake trout, Salvelinus namaycush (Walbaum), omnivory or in any of the assessed quantitative food web metrics. Gut contents of major fish species similarly showed significant temporal overlap between the pre‐ and post‐introduction periods, and there was no significant change in species' weight–length relationships. The minor ecological impact was interpreted in relation to the availability of open niches exploitable by ecological generalists such as Arctic charr. The explanation accords with the known habitat and feeding flexibility of Arctic charr and the ecological immaturity of sub‐Arctic lakes known to have driven adaptive variation among Arctic charr. Findings suggest that anadromous Arctic charr may be introduced at moderate densities to other sub‐Arctic watersheds without major negative food web consequences for other resident fish species.